Contributions to the Andean Senecioneae (Compositae)—II. Werneria lanatifolia, a new species from central Andes - Calvo, Joel; Meneses, Rosa I. (Phytotaxa, 2019)
Werneria lanatifolia is described as a new species from the central Andes. It is a minute plant characterized by a lanate indumentum on the adaxial leaf surface and involucre. The new species is compared with the morphologically closest taxa and useful characters for its proper identification are provided. Detailed pictures of living plants, a distribution map, and a dichotomous key including the species allied to W. lanatifolia are also presented.